2018
DOI: 10.18203/2349-3291.ijcp20180981
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of meconium aspiration syndrome in relation to birth weight and gestational age

Abstract: Background: Meconium aspiration syndrome (MAS) is commonly encountered entity in neonates delivered in rural health centres.Methods: A prospective observational study was conducted in 50 consecutive cases of MAS who were admitted in Level III NICU of the Department of Pediatrics of a tertiary care teaching hospital located 50 kms from Jaipur city amidst rural surroundings from 1st January 2016 to 31st July 2017. Appropriate statistical analysis was carried out using Medcalc statistical software (version 16.4).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Similar results were found by study done by Nath et al and showed that incidence of MAS was 6.5% cases, whereas Garg et al found 8.5% incidence rate of MAS in their study. 6,7 Present study which was conducted over 96 new born with MAS, male new borns were more affected i.e 59 (61.45%) than female newborns 37 (38.54%) (Table 1). Similar results were found by Garg et al with male: female ratio of 1.2:1 and the study by Ramakishore et al concluded that among affected babies, male were 58% and females were 42%.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar results were found by study done by Nath et al and showed that incidence of MAS was 6.5% cases, whereas Garg et al found 8.5% incidence rate of MAS in their study. 6,7 Present study which was conducted over 96 new born with MAS, male new borns were more affected i.e 59 (61.45%) than female newborns 37 (38.54%) (Table 1). Similar results were found by Garg et al with male: female ratio of 1.2:1 and the study by Ramakishore et al concluded that among affected babies, male were 58% and females were 42%.…”
Section: Discussionmentioning
confidence: 91%
“…In the study done by Garg et al maximum number of cases of meconium aspiration syndrome 60% were seen in neonates with birth weight between 2500-3500 g, followed by neonates with birth weight less than 2500 g (34%). 7 Singh et al also observed that MAS was more common in babies with gestational age >37 weeks. 14 In our study, out of 96 cases 53.1% babies were managed conservatively with oxygen support, restricted intra venous fluid, antibiotics and 46.8% babies needed ventilator support.…”
Section: Discussionmentioning
confidence: 94%
“…15 Respiratory distress in a neonate born through MSAF with radiographic changes of aspiration pneumonitis may be defined as Meconium aspiration syndrome. 16 About 5% of the babies born through meconium stained amniotic fluid develop meconium aspiration syndrome and the mortality rate of these babies vary from 4-7%. 17 In deliveries complicated with MSAF, there is an increased risk of caesarean section, chorioamnionitis and puerperal sepsis along with higher morbidity and mortality in mother while the unfavorable outcomes in neonate include increased risks of birth asphyxia and fetal distress, low Apgar scores, increased incidence of neonatal intensive care unit (NICU) admission, meconium aspiration syndrome and early neonatal death.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported a higher proportion of meconium aspiration syndrome amongst new born with higher gestational age. 18,21 A study conducted in India reported a higher proportion of SVD in newborns with meconium aspiration syndrome in their study. 18 Similar to our study findings, the mortality rate was also found consistent with a studyconducted in North America.…”
Section: Discussionmentioning
confidence: 89%